Prevalence of thyroid dysfunction in the general population in Erbil city - Mousa khaleel, Khoshawi; Ghulam Hussain, Saeed (Zanco Journal of Medical Sciences (ZJMS), 2025)
Background and objectives: Thyroid diseases are worldwide endocrine disorders in clinical practice. Risk prevalence is higher in females than males with significant clinical adverse effects among these cardiovascular diseases. Prevalence is high among diabetic patients; with subclinical hypothyroidism categorized as the most common endocrine disorders. The aim of the present study was to screen the prevalence of thyroid dysfunction among apparently healthy adults, with special reference to diabetic patients. Methods: 300 apparently healthy adults’ thyroid free disorders were screened included 200 females &100 males individuals of different age & BMI. Blood samples were collected & subjected to. thyroid profiles test included TSH, FT3 &FT4.Thyroid dysfunction-were further categorized according to the tested thyroid profiles. Results: The results revealed 7.3 % prevalence of sub-clinical hypothyroidism followed by overt hypothyroidism (1.7%) & subclinical hyperthyroidism (0.7%). Among diabetic patients subclinical hypothyroidism predominate (12.5%) followed by clinical hypothyroidism (7.5%). Conclusion: The results delineated the fact that among thyroid free subjected, screening in of paramount importance especially diagnosis of subclinical hypothyroidism that might linked with significant clinical complication especially female during pregnancy & as a cardiovascular diseases risk factor.